Inside the rainbow : Russian children's literature, 1920-35 : beautiful books, terrible times - Rothenstein, Julian; Budashevskai︠a︡, O. (London : Redstone, 2013)
"Inside the rainbow' reprints for the first time in English a unique compendium of Soviet picture books from the 1920 and 1930s - a highpoint in the history of children's literature. In the dark and dangerous world of revolutionary Petrograd, a group of Russian poets and artists, among the greatest of the century, came together to create a new kind of book for children about to enter a Brave New World. ...These artists and writers dreamed of endless possibilities in a new world where children and grown-ups alike would be free from the bitterness of ignorance. For a time, when children's publications still escaped the scourge of state censorship, their books became a last haven for learning, poetic irony, burlesque and laughter. In this book 250 examples of illustration and design are complemented by some wonderful translations of poems and stories as well as texts from the victims, criminals and witnesses to the Russian revolution..." -- back cover
boek